2018
DOI: 10.1111/ajco.12874
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary efficacy and tolerability of chemohormonal therapy in metastatic hormone‐naïve prostate cancer: The first real‐life experience in Asia

Abstract: Early efficacy with chemohormonal therapy in Asian mHSPC patients was comparable to the pivotal study and biochemical response is promising. The high frequency of hematologic toxicities in Asian patients highlights the importance of proper patient selection and pre-emptive use of granulocyte colony-stimulating factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 20 publications
4
21
0
Order By: Relevance
“…The rates of FN reported in randomized controlled trials ranged from 0.9% in TAX 327, 1 3% in GETUG‐AFU 15, 6 and 6.2% in CHAARTED, 3 to 15% in STAMPEDE 4 . Our previous real‐world data suggested that, compared with Western populations, Chinese patients may experience more frequent hematologic toxicities such as neutropenia, FN, and anaemia, 7 in accordance with genetic association findings on increased susceptibility to myelosuppression in Asian populations 8 . The rates of FN in these studies were 12.5% for patients with mHSPC who received docetaxel plus hormonal therapy, 7 and 14.0% for mCRPC patients treated with docetaxel‐based chemotherapy 8 .…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The rates of FN reported in randomized controlled trials ranged from 0.9% in TAX 327, 1 3% in GETUG‐AFU 15, 6 and 6.2% in CHAARTED, 3 to 15% in STAMPEDE 4 . Our previous real‐world data suggested that, compared with Western populations, Chinese patients may experience more frequent hematologic toxicities such as neutropenia, FN, and anaemia, 7 in accordance with genetic association findings on increased susceptibility to myelosuppression in Asian populations 8 . The rates of FN in these studies were 12.5% for patients with mHSPC who received docetaxel plus hormonal therapy, 7 and 14.0% for mCRPC patients treated with docetaxel‐based chemotherapy 8 .…”
Section: Introductionmentioning
confidence: 85%
“…Our previous real‐world data suggested that, compared with Western populations, Chinese patients may experience more frequent hematologic toxicities such as neutropenia, FN, and anaemia, 7 in accordance with genetic association findings on increased susceptibility to myelosuppression in Asian populations 8 . The rates of FN in these studies were 12.5% for patients with mHSPC who received docetaxel plus hormonal therapy, 7 and 14.0% for mCRPC patients treated with docetaxel‐based chemotherapy 8 . Similarly, a recent real‐world study in Korea reported an FN rate of 22.5% during the first cycle of docetaxel in mCRPC patients 9 …”
Section: Introductionmentioning
confidence: 99%
“…Although the relationships between genetic ethnic disparities and clinical outcomes in PC are somewhat unclear, the differences between Asian and White patients in chemotherapy tolerance have been well established. In our reports of real-world experience using docetaxel in Chinese patients with mHSPC as well as mCRPC, we found much higher incidences of haematological complications, particularly febrile neutropenia (FN), compared with studies in Western populations [ 22 , 23 , 24 , 25 ] ( Table 1 ). Furthermore, real-world data for cabazitaxel in international compassionate use and early access programmes revealed similarly elevated rates of myelosuppression among Asian patients [ 26 , 27 ].…”
Section: Drug Tolerability In Asian Patientsmentioning
confidence: 85%
“…Forty-seven were removed as duplicates due to overlapping among databases. After screening the titles and abstracts and then the full texts, 27 publications 17 43 were shortlisted. No additional studies were identified from the bibliographic search.…”
Section: Resultsmentioning
confidence: 99%